PEMASARAN KAIN TENUN DI KELOMPOK TENUN LEMBANG KOLE BARABATU KABUPATEN TANA TORAJA - Daeng Toto, Herenal; -, Fatmasari; Bahtiar, Akbar; Muslaini, Fadel (Arunika: Jurnal Pengabdian Masyarakat, 2022)
This digital marketing training activity aims to provide an understanding of optimizing the use of social media as a marketing medium. The participants involved in this digital marketing workshop consisted of 8 people who were woven fabric craftsmen in Lembang Kole Barabatu, Tana Toraja Regency. The material presented in the implementation of this community service focused on discussions related to "marketing strategies for several online media as a means of product marketing". The outline of the discussion consists of Strengths, Optimization Steps, Determining the Market, Maximizing Profit and Name, Posting Material, Maintaining Rhythm and Timeline Patterns, Narrative and Timing, Changing Personal Accounts to Business Accounts, Reading and Learning Insights, Building Targeted Followers, Tools Supporters and Safe Tips for transacting in cyberspace